-8(v*3)-7v=-4+10(1-v)

Simple and best practice solution for -8(v*3)-7v=-4+10(1-v) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(v*3)-7v=-4+10(1-v) equation:


Simplifying
-8(v * 3) + -7v = -4 + 10(1 + -1v)

Reorder the terms for easier multiplication:
-8(3v) + -7v = -4 + 10(1 + -1v)

Remove parenthesis around (3v)
-8 * 3v + -7v = -4 + 10(1 + -1v)

Multiply -8 * 3
-24v + -7v = -4 + 10(1 + -1v)

Combine like terms: -24v + -7v = -31v
-31v = -4 + 10(1 + -1v)
-31v = -4 + (1 * 10 + -1v * 10)
-31v = -4 + (10 + -10v)

Combine like terms: -4 + 10 = 6
-31v = 6 + -10v

Solving
-31v = 6 + -10v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '10v' to each side of the equation.
-31v + 10v = 6 + -10v + 10v

Combine like terms: -31v + 10v = -21v
-21v = 6 + -10v + 10v

Combine like terms: -10v + 10v = 0
-21v = 6 + 0
-21v = 6

Divide each side by '-21'.
v = -0.2857142857

Simplifying
v = -0.2857142857

See similar equations:

| 9k-21=3(k-7)+6k | | 25(35h)=40h | | -23+x+28= | | -2x-8=8x+1 | | 3x(2xy^2+4y^3)=V | | (4x+3)(3x-5)=(4x-3)(3x+5) | | 12x+50=7x-40 | | 5x-5=5(x+7) | | 6+13=6+(n+5) | | .12222= | | 5c+c=78 | | -5x+13=14 | | -2=20x | | 6n^2-18n-168=0 | | 12m-15=-3 | | 3x-0.4=1.4 | | Y+28=x+5 | | 8(x+3)-3x=2(x+12)+3x | | B+ax=2x | | -7v-19=6(1+3v) | | -5(x+3)+8=-7 | | 36w=648 | | 0.4(-5)+6.1= | | 6u^2+u-6=0 | | -2(t-2)+7t=9T-3 | | 3x+7+6x=106 | | -3(y-2)=-2y-1 | | ln(x+1)+ln(3)=ln(2x) | | x-15=4y | | 5.25n=46.50 | | 5*(12-3)=5*e | | 15n=5.25 |

Equations solver categories